Exploring Vocabulary Characteristics Across Nine Music Genres: A Corpus-Based Study for Vocabulary Learning - Nonthasen, Nonthawat; Samakketwit, Sinaphat; Srisompak, Patsarapa; Laosrirattanachai, Piyapong (Studies in English Language and Education, 2025)
The use of music for vocabulary learning has been extensively researched, yet there remains a gap in studies focusing on vocabulary across different music genres. This study aims to examine the vocabulary characteristics of nine music genres. Data were collected from Billboard and YouTube songs between 2014 and 2023, categorising the songs into nine genres, forming a corpus of 671,051 tokens. The study analysed five aspects of vocabulary. The findings are as follows: 1) Lexical profiling: Jazz covers the highest percentage of words from the GSL (91.33%), while hip-hop has the lowest (78.88%). Hip-hop also includes the highest percentage of OWL words (20.52%). 2) Lexical Level: Country and folk, jazz, and alternative have the highest use of high-frequency words (K1-K3) at 95.20%, 94.74%, and 94.23%, respectively, while hip-hop has the lowest (87.01%) but employs the most mid-frequency (K4-K9) and low-frequency words (K10-K25) at 4.06% and 8.93%, respectively. 3) CEFR: Beginners (A1-A2) should listen to country and folk, jazz, alternative, and rock. Intermediate learners (B1-B2) are best suited to RB/soul, children, pop, and electronic. Advanced learners (C1-C2) should choose hip-hop. 4) Lexical variation: Jazz (43.44%) and children (39.73%) exhibit the highest vocabulary variation. 5) Lexical density: Hip-hop has the highest lexical density at 52.88%, followed by children (51.80%) and RB/soul (50.25%). These findings provide guidance for selecting music genres to enhance vocabulary learning at different proficiency levels, both in and out of the classroom.